Efficacy of a novel food supplement in the relief of the signs and symptoms of seasonal allergic rhinitis and in the reduction of the consumption of anti-allergic drugs - Ariano, Renato (Acta Biomedica Atenei Parmensis, 2015)
Background: Seasonal Allergic rhinitis (SAR) is characterized by runny nose, congestion, sneezing and sinus pressure. A clinical study was performed to demonstrate the efficacy of Lertal®, an innovative food supplement containing Quercetin, Perilla frutescens and Vitamin D3 formu-lated in a double layer “fast-slow” release tablet form, in the relief of symptoms of seasonal allergic rhinitis and in the reduction of consumption of anti-allergic drugs. Patients and methods: 23 subjects enrolled in the open clinical study had at least one year history of allergic rhinitis and positive skin prick test or RAST to Parietaria officinalis pollen. At baseline, the subjects had symptoms of nasal and/or ocular seasonal allergic rhinitis. The activity of the food supplement was evaluated using the Total Symptoms Score at first (baseline) and second (final) visit, after one month of supplementation. The consumption of anti-allergic drugs was also evaluated. Results: All subjects enrolled completed the study. The comparison of the scores obtained in the two visits (baseline and final) showed a highly significant reduction of the overall symptoms: approximately 70% for symptom scores and 73% in use of anti-allergic drugs. Sneezing, rhinorrhea, nasal obstruction, ocular itching, lacrimation and congestion of the conjunctiva, all showed a highly significant reduction. No noteworthy side effect was recorded and all patients finished the study with good compliance. Conclusions: The results showed a clear efficacy of the food supplement Lertal® in reducing nasal and/or eye symptoms. This activity was objectively confirmed by the reduction in the consumption of anti-allergic drugs used to relieve symptoms. (www.actabiomedica.it)